Excitability and coherence resonance of DFB laser with passive dispersive reflector - Tronciu, Vasile (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2008)

(untitled)
We investigate the phenomena of excitability and coherence resonance of single mode